Antigenicidade e atividades biológicas do veneno hemorrágico da serpente crotalus durissus ruruima (Hoge 1965), após indução da proteólise das toxinas “IN VITRO” - Catunda, João Paulo Gonçalves (2010)
Currently, more than two hundred species of poisonous snakes have have been identified, they are classified into four main families: Hydrophiidae; Elapide, Viperidea and Crotalidae, the genus crotalus presents higher lethality rate (1.87%), due to neurotoxicity and insufficiency acute renal failure which is the most serious complication of crotalic poisoning the poison present in the snake Crotalus durissus ruruima was introduced into mice to assess biological characterization and antigenicity of these. The procedures performed were the characterization of the molecular profile of in natura and proteolyzed poisons, immunization of mice with T0 and T6 antigens, tests to neutralize the lethality of the poison using experimental hyperimmune plasma, immunochemical analysis for verification of the antigen-antibody reaction and statistical tests. From this experiment among other results, it was observed that the molecular profile showed variations in the detection of the bands and also in the quantitative analysis of the proteins, in the zymogram on fibrinogen and gelatin the intensity of the bands showed variations but proteolyzed samples when compared with the poison in natura, the experimental hyperimmune serum T6 obtained better neutralizing response when compared to T0 serum, in the lethality test mice are more resistant when given venom serum proteolyzed proteolyzate taking longer to die, the mice immunized with T0 did not resist the challenge dose of 5 LD50 dying, the mice immunized with T6 immune response, showing none of the symptoms caused by the poison and survived the challenge dose of 5 LD50.